2011
DOI: 10.1183/09031936.00103411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mediterranean dietversusprudent diet combined with physical activity on OSAS: a randomised trial

Abstract: We aimed to evaluate the effect of the Mediterranean diet (MD) compared with a prudent diet (PD) combined with physical activity on obese obstructive sleep apnoea syndrome (OSAS) patients who were treated with continuous positive airway pressure. 900 patients were evaluated and 40 obese patients (body mass index o30.0 kg?m -2 ) who met the inclusion criteria, with moderate-to-severe OSAS (apnoea-hypopnoea index (AHI) .15 events?h -1 and Epworth Sleepiness Scale score .10) based on overnight attended polysomnog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 50 publications
(47 reference statements)
3
51
0
4
Order By: Relevance
“…Very low energy diets have been widely used according to a variety of protocols; however, there are only two diets that have been tested against each other specifically in OSA patients, the Mediterranean diet versus the prudent diet [77]. The AHI during rapid eye movement sleep was reduced in the Mediterranean diet group compared to the prudent diet.…”
Section: Osa and Liver Damagementioning
confidence: 99%
See 2 more Smart Citations
“…Very low energy diets have been widely used according to a variety of protocols; however, there are only two diets that have been tested against each other specifically in OSA patients, the Mediterranean diet versus the prudent diet [77]. The AHI during rapid eye movement sleep was reduced in the Mediterranean diet group compared to the prudent diet.…”
Section: Osa and Liver Damagementioning
confidence: 99%
“…Recent evidence suggests that exercise training may be associated with a reduction in OSA severity [78,87,88,90] and, not surprisingly, improved exercise capacity [84,85,87,91]. Exercise alone may also improve OSA severity without significant weight loss [77,88,90]. More specifically, KLINE et al [91] tested the effects of aerobic exercise for 4 days per week in a supervised environment at moderate intensity (equating to 150 minutes per week) combined with resistance training.…”
Section: Osa and Liver Damagementioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence in OSAS supports the beneficial role of weight reduction, induced by diet alone [9][10][11][12] or in combination with exercise [13], leading to a reduction in apnoeas and hypopnoeas. A recent study conducted at the University of Crete examined the effect of the Mediterranean diet (MD) compared with that of a prudent diet on obese adults with moderate-to-severe OSAS who were treated with CPAP while receiving counselling to increase their physical activity [14]. The results showed that people following the MD had a reduced number of disturbances, known as apnoeas, during the rapid eye movement (REM) stage of sleep, which usually accounts for approximately 25% of total sleep during the night.…”
Section: Editorialmentioning
confidence: 99%
“…Although data addressing weight loss in OSA patients are somewhat limited, the data available suggest that weight loss can be a highly effective treatment in the short term [7]. Such patients should also be followed closely because OSA may recur even in patients who maintain their weight loss [8].…”
mentioning
confidence: 99%